Development and Validation of the Online Student Connectedness Survey (OSCS) - Bolliger, Doris U; Inan, Fethi A (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
With the growth of online courses and programs in higher education, considerable concerns emerge about student feelings of isolation and disconnectedness in the online learning environment. A research study was conducted to develop and validate an instrument that can be used to measure perceptions of connectedness of students enrolled in online programs or certification programs in higher education. The instrument consists of 25 items and has four scales: (a) community, (b) comfort, (c) facilitation, and (d) interaction and collaboration. One hundred and forty-six online learners who were enrolled in courses at a Turkish university completed the online questionnaire. Results of a factor and reliability analysis confirmed that the instrument is a valid and reliable measure of students’ perceived connectedness in an online certificate program.